Genetically modified food crops and their contribution to human nutrition and food quality - Bouis, Howarth E.; Chassy, Bruce M.; Ochanda, James O. (Wiley, 2004)
Modern genetic modification is one of the tools to help feed the world, now and in the future. Its particular value lies in its ability to produce results faster, to be targeted better than other methods, and, in some instances, to achieve results that cannot be effectively obtained by other means. Potential benefits include: greater crop output from reduced input (energy, labor, other costs); reduction in use of chemical pesticides; crops with improved nutrition characteristics; crops that can grow under inhospitable conditions; and crops with improved handling and processing characteristics. Like any new technology it has potential problems, some real, some speculative, and some imaginary. However, we are not disinterested bystanders on the sidelines noting problems and regarding them as possible reasons not to proceed. Science is society's tool for addressing and solving problems so that useful potentialities can be realized, especially for a growing population that needs to be adequately fed.